Pengaruh Kinerja Keuangan DER dan ROE Terhadap Perubahan Harga Saham pada Perusahaan Manufaktur yang Terdaftar di BEI (Periode 2009-2013) - Syamsu Rizal; Fira Permatasari (Universitas Bandar Lampung (UBL), 2015)
This study aims to identify and analyze the effect of Debt to Equity Ratio (DER) and Returnon Equity (ROE) financial performance on the change of stock prices in the manufacturing companies listed on the Indonesia Stock Exchange 2009-2013 . The hypothesis was first put forward in a positive and significant effect of DER on the change of stock prices in the manufacturing companies listed on the Indonesia Stock Exchange, the second hypothesis is the positive and significant effect on the ROE on the change of stock prices in the manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study is the subsector of plastic and packaging companies that are listed in Indonesia Stock Exchange2009-2013. Sampling using purposive sampling in order to obtain a total sample of 6 plastic and packaging companies that meet the criteria of the study sample set. Financial performance is measured using Debt Equity Ratio (DER) and Return on Equity (ROE). The technique of data analysis done with the classical assumption, hypothesis testing using multiple linear regression analysis using SPSS 18.0 for windows . The results showed that in partial, both of DER and ROE has positive influence on the change of stock prices in the subsector of plastic and packaging companies that are listed in the Indonesia Stock Exchange.